STUDI HABITAT TEMPAT BERTELUR PENYU HIJAU (Chelonia mydas) DI KAWASAN TAMBLING WILDLIFE NATURE CONSERVATION (TWNC) TAMAN NASIONAL BUKIT BARISAN SELATAN (TNBBS) TANGGAMUS PESISIR BARAT - Rohim, Hairul; Rifanjani, Slamet; Erianto, . (Universitas Tanjungpura, 2017)
This study aims to determine the nesting habitat of Green Turtle (Chelonia mydas) in the Tambling Wildlife Nature Conservation (TWNC) Bukit Barisan Selatan National Park (TNBBS) Tanggamus West Coast. We collected a variety of data to describe the habitat and nests used. The data collected include: the length of the beach, the slope and width of the beach, the size of the nest, the temperature of the nest, air temperature and humidity, salinity, texture of sand, and the presence of factors that influence sea turtle conservation. From Belimbing beach to Sekawat beach, we found that beach lengthwas 18.075 meters, the slope of the coast ranged 6-15%, the beach width ranged 21-50 meters at low tide and 5-17 meters at high tide, %, the nest hole circumference averaged 414,66 cm,the nest temperature ranged 27,05â°C to 38,55â°C,the air temperature ranged 30,8â°C-26,8â°C, the humidity ranged 72.6%-62.93, the depth of the nest averaged 56 cm, the salinity of the sea water averaged 30.3 â€°, and the fine sand fraction ranged 0,10-0,21 mm. Green Turtles are threatened by the presence of predators such as Monitor Lizard (Varanus salvator) and ghost crab(Ocypoda sp.), as well as by human activity.Trawl fishing in the ocean also could affect sea turtle conservation. Keyword: Green Turtle, physical characteristics, nesting habitat.